Relationship of Night Shift Work and Breast Cancer - Arnold Fernando; Muhammad Ilyas; Indah Suci Widyahening (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Background. Breast cancer is the most common cancer among women worldwide. 80% of breast cancer that has been identified in Indonesia has progressed into an advanced stage of malignancy. In 2007, the International Agency for Research on Cancer concluded: shift-work that involves circadian disruption is probably carcinogenic to humans (Group 2A) Aim. This study aims to justify the association between night shift work and breast cancer. Methods. Searching literature for the evidence-based has been conducted with a clinical question through